Influence of mouth rinsing a carbohydrate solution on 1-h running performance - Rollo, I.; Cole, M.; Miller, R.; Williams, C. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The aim of this study was to investigate the influence of mouth rinsing a CHO-electrolyte (CHO-E) solution on 1-h running performance. A second study determined whether mouth rinsing a CHO-E solution altered the blood glucose and plasma insulin concentrations at rest.